Gender Equality Prior to and Following Separation: Nordic and Liberal Policy Inconsistencies - Hakovirta Mia; Cook Kay; Sinclair Sarah (Oxford University Press, 2025)
We compare family policy in Australia and Finland, focusing on child support as interrogating how gender equality ideals and realities play out when families diverge from the dual-parent model. Despite Finland’s de-gendered leave and employment policy, a gender wage gap continues to position mothers as primary carers. In Australia, pre-separation policies are gendered in that leave benefits position mothers as primary carers. In both countries, child support policy took the opposite approach. Finland’s child support policy provides less incentive for the father to take care of children post-separation.